PRAKTIK AKUNTANSI BERDASARKAN KONSEP DASAR AKUNTANSI : Pada Usaha Kecil Toko Tas Wanita Karebosi Link Makassar - Nurmawaddah (Melati Institute, 2023)
Every business that is run regardless of the form of the company, should have good accounting records according to the basic concepts of accounting that apply. However, in reality what happens in the field is that there are still many small companies that have not applied the basic concepts of accounting in recording every economic activity in their trading activities. This study aims to determine whether the accounting practices applied to the women's bag shop business at Karebosi Link Makassar are in accordance with the basic concepts of accounting. The data collection methods that the author uses are structured interviews, observations and documentation. As for data analysis, the authors use descriptive methods. The population in this study were ten (10) women's bag shops in Karebosi Link Makassar. Based on the results of research and discussion, it is obtained that the women's bag shop at Karebosi Link Makassar has carried out bookkeeping records, but it is still not appropriate, so it can be concluded that the women's bag shop at Karebosi Link Makassar has implemented accounting practices but it is done simply and not in accordance with the basic concepts of accounting.